Species distribution modeling for the invasive raccoon dog (Nyctereutes procyonoides) in Austria and first range predictions for alpine environments - Duscher, Tanja; Nopp-Mayr, Ursula (Archives of Biological Sciences, 2017)
Species distribution models are important tools for wildlife management planning, particularly in the case of invasive species. We employed a recent framework for niche-based invasive species distribution modeling to predict the probability of presence for the invasive raccoon dog (Nyctereutes procyonoides) in Austria. The raccoon dog is an adaptive, mobile and highly reproductive Asiatic canid that has successfully invaded many parts of Europe. It is known to occur in Austria since 1963 and is now widespread in the northern and eastern parts of the country, but its population density remains low. With the help of a species distribution model we identified focal areas for future monitoring and management actions, and we address some management implications for the raccoon dog in Austria. We also determined the environmental predictors of raccoon dog distribution in this alpine country. Its distribution seems to be mainly limited by climatic factors (snow depth, duration of snow cover, winter precipitation and mean annual temperature) and is thus linked to elevation. Consequently, we assumed the Alps to be a barrier for the spread of the invasive raccoon dog in Europe; however, its ecological permeability is expected to increase with ongoing climate change. https://doi.org/10.2298/ABS161124009D Received: November 24, 2016; Revised: February 17, 2017; Accepted: March 1, 2017; Published online: March 16, 2017 How to cite this article: Duscher T, Nopp-Mayr U. Species distribution modeling for the invasive raccoon dog (Nyctereutes procyonoides) in Austria and first range predictions for alpine environments. Arch Biol Sci. 2017;69(4):637-47.